Greenhouse Gas Emissions and Carbon Sinks of an Italian Natural Park - Grossi, Giampiero; Vitali, Andrea; Bernabucci, Umberto; Lacetera, Nicola; Nardone, Alessandro (Frontiers in Environmental Science, 2021)
Natural parks (NPs) have a primary role in supporting people’s welfare by maintaining the natural and cultural resources. Within the boundaries of a NP may coexist various activities such as the conservation of flora and fauna, forestry, agriculture and livestock, residential, and tourism. All these activities may contribute as source or sink of carbon dioxide and, despite some NPs have started to promote their environmental services, currently there is a lack of information on their carbon footprint (CF). Although various international standards have provided guidelines to assess the CF of organizations, a lack of explicit formulation and procedure in these standards makes them difficult to apply, especially when the organizations to be evaluated embed a wide range of biological and anthropogenic activities. To fill this gap, the framework proposed in this paper provides a holistic methodological approach to quantify and report the annual greenhouse gas (GHG) emissions and removals occurring on NPs. The main data needed for the NP's GHG inventory were directly collected on-site, the activity data and emissions factors as well as the methodologies involved were all referenced to their data sources, which have included: the use of a biogeochemical model, IPCC equations, ecoinvent database, and literature review. This method highlighted that, by emitting 0.55 Mg CO2e hectare-1 year-1, the NP generates an annual CF of about 3,300 Mg of CO2e. The agricultural activities with 43.4% of share showed the largest incidence, followed by wild fauna (17.8%), tourism (15.1%) and to a lesser extent, by all the other sectors considered in the assessment. On the other hand, when the annual soil and forest C sequestration rates were included in the balance, the NP contributes to sequester about 3.7 Mg CO2e hectare-1 year-1, thus resulting as an important C-sink site (i.e., about 22,000 Mg CO2e year-1). By providing granular information on GHG emissions and carbon removals trend, the methodological approach involved in this study resulted suitable to be implemented on CF assessments of NPs. CF of NPs could increase the people awareness on the important role that these protected natural areas have in climate change mitigation and adaptation.